Answering the Bell: High School Start Times and Student Academic Outcomes - Kevin C. Bastian; Sarah C. Fuller (SAGE Publishing, 2018)
We contribute to the school start time literature by using statewide student-level data from North Carolina to estimate start time effects for all students and for traditionally disadvantaged students. Descriptively, we found that urban high schools were likely to start very early or late. Later start times were associated with positive student engagement outcomes (reduced suspensions, higher course grades), especially for disadvantaged students. Achievement results were mixed, with positive and negative associations between start times and high school students' test scores. Continued research is necessary to evaluate the efficacy of later start times as a scalable and cost-effective approach for boosting engagement and achievement.